2022
DOI: 10.1155/2022/4026688
|View full text |Cite
|
Sign up to set email alerts
|

Caudatin Inhibits the Proliferation, Invasion, and Glycolysis of Osteosarcoma Cells via the Wnt/β- Catenin Pathway

Abstract: Background. Caudatin is a steroidal glycoside with reported anticancer activity in a variety of studies. Nevertheless, the role and mechanisms of caudatin in osteosarcoma (OS) remain unclear. In this study, we explored the potential anticancer effects of caudatin in OS cells and investigated the underlying mechanisms. Methods. Both the CCK8 proliferation assay and flow cytometry were employed to evaluate cell proliferation and apoptosis. A transwell assay was applied to determine cell invasion ability. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Currently, many anticancer drugs or genes have been found to improve tumor progression in osteosarcoma and other cancers by reversing the “Warburg effect” and suppressing glycolysis. For example, Caudatin, a naturally occurring steroidal glycoside with anticancer activities, was found to inhibit osteosarcoma cell proliferation and invasion by suppressing glycolysis ( Zhang et al, 2022 ). Deng et al (2022) showed Ubiquitin-like protein FAT10 could promote osteosarcoma glycolysis and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many anticancer drugs or genes have been found to improve tumor progression in osteosarcoma and other cancers by reversing the “Warburg effect” and suppressing glycolysis. For example, Caudatin, a naturally occurring steroidal glycoside with anticancer activities, was found to inhibit osteosarcoma cell proliferation and invasion by suppressing glycolysis ( Zhang et al, 2022 ). Deng et al (2022) showed Ubiquitin-like protein FAT10 could promote osteosarcoma glycolysis and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is speculated that apigenin inhibits the Warburg effect and cell proliferation of OS cells by inhibiting the PI3K/Akt/mTOR signaling pathway. Research [136] has found that caudatin inhibits cellular glycolysis by reducing the expression of HK2 and LDHA, possibly by downregulating the expression of β-Catenin, Cyclin D1, and C-myc to inhibit the Wnt/β-catenin signaling pathway, thereby affecting the glycolysis process, and ultimately achieving the goal of inhibiting the proliferation and metastasis of OS cells [136] . Resveratrol inhibited the proliferation and glycolysis of OS cells by inhibiting the activity and downstream gene expression of Wnt/β-catenin signaling pathway and enhancing the expression of Cx43 and e-cadherin genes [137] .…”
Section: Potential Therapeutic Effects Of Drugs Targeting Glucose Met...mentioning
confidence: 99%